COMPUTATIONAL STUDIES ON DIFFERENT TYPES OF APOPTOTIC PROTEINS DOCKED WITH A DIETARY FLAVONOID ERIODICTYOL IN COLON CANCER - Palani, Mariyappan; Natesan, Karthi; Vaiyapuri, Manju (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: In this study, to evaluate the computational studies of eriodictyol docked with apoptotic proteins. Methods: AutoDock Vina and Molecular Graphics Laboratory tools were used to determine the interaction between proteins and eriodictyol. Discovery studio visualizer and PyMOL were used to determine the interaction of amino acid residues between apoptotic proteins and eriodictyol. Results: The obtained results revealed more binding affinities of p53, caspase 8, B-cell lymphoma (Bcl)-2, Bcl-2 - associated X protein (BAX), and adenomatous polyposis coli (APC) of âˆ’10.6, âˆ’10.9, âˆ’9.0, âˆ’9.5, and 7.2 kcal/mol, respectively. Interaction of hydrophobic polar contacts of amino acid residues of p53 (CYS-277 and ALA-276), caspase 8 [THR-467, THR-337 (2), and GLU-396 (2)], Bcl-2 [ARG-103 (3), ALA-104 (2), and PHE-105, TYR- 101], BAX [GLY-108, TRY-107, ASN-106, and GLN-155 (2)], and APC [GLU-40 (2) and LEU-37 (2)] were notified between macromolecules and small molecules. The calculation of root-mean-square deviation of proteins and eriodictyol showed the lower binding energies to be 11.6, 12.5, 15.9, 19.6, and 15.8 and the upper binding energies to be 12.4, 15.3, 16.9, 20.7, and 18, respectively. The homology of binding energies was determined below 2Ã… which is computationally less expensive and easily determined the hydrophobic polar contacts. Conclusions: TheÂ homologyÂ ofÂ bindingÂ energiesÂ wasÂ determinedÂ belowÂ 2Ã… whichÂ isÂ computationallyÂ lessÂ expensive Â andÂ easilyÂ determined the hydrophobic polar contacts. The results were proved that the eriodictyol highly interacted with apoptotic proteins. It might be a strong anti-inflammatory activity of colon cancer. In future, computational molecular docking studies should aid further in vitro and in vivo studies. Keywords: AutoDock Vina, p53, Eriodictyol, Caspase 8, B-cell lymphoma-2, Bcl-2 - associated X protein, Adenomatous polyposis coli.